Directed evolution predicts cytochrome b G37V target site modification as probable adaptive mechanism towards the QiI fungicide fenpicoxamid in Zymoseptoria tritici. (16th September 2021) - Fouché, Guillaume; Michel, Thomas; Lalève, Anaïs; Wang, Nick X.; Young, David H.; Meunier, Brigitte; Debieu, Danièle; Fillinger, Sabine; Walker, Anne‐Sophie
Summary: Acquired resistance is a threat to antifungal efficacy in medicine and agriculture. The diversity of possible resistance mechanisms and highly adaptive traits of pathogens make it difficult to predict evolutionary outcomes of treatments. We used directed evolution as an approach to assess the resistance risk to the new fungicide fenpicoxamid in the wheat pathogenic fungus Zymoseptoria tritici . Fenpicoxamid inhibits complex III of the respiratory chain at the ubiquinone reduction site (Qi site) of the mitochondrially encoded cytochrome b, a different site than the widely used strobilurins which inhibit the same complex at the ubiquinol oxidation site ( Q o site). We identified the G37V change within the cytochrome b Q i site as the most likely resistance mechanism to be selected in Z . tritici . This change triggered high fenpicoxamid resistance and halved the enzymatic activity of cytochrome b, despite no significant penalty for in vitro growth. We identified negative cross‐resistance between isolates harbouring G37V or G143A, a Q o site change previously selected by strobilurins. Double mutants were less resistant to both QiIs and quinone outside inhibitors compared to single mutants. This work is a proof of concept that experimental evolution can be used to predict adaptation to fungicides and provides new perspectives for the management of QiIs.